Pengaruh Kompensasi dan Motivasi terhadap Kinerja Karyawan pada PT XYZ Karawang - Kevin Fewa Morando; Edi Suswardji Nugroho; Solehudin Solehudin (Syntax Literate, 2021)
The purpose of this study was to determine the effect of compensation and motivation on the performance of employees of PT XYZ Karawang. The research was conducted by distributing questionnaires, while the research method used Simple Random Sampling for the sampling technique. The results of the t test show that the tcount for the compensation variable (X1) is 2.832 and the tcount for the motivation variable (X2) is 6.167. From the two tcount, it shows that it is bigger than ttable, which is 1.65882. The hypothesis which states that compensation and motivation have a partially positive effect on employee performance at PT XYZ Karawang. Whereas from the results of the F test, Fcount> Ftable or 55.860> 3.08 or the significance level (sig) 0.000 <0.05 so that the hypothesis that states compensation and motivation together has an effect on employee performance at PT XYZ Karawang and the coefficient of determination shows that compensation and work motivation contributed 51.1% to Employee Performance at PT XYZ Karawang, the remaining 48.9% were other factors which were not examined in this study.